Simulation of vibration and noise of belt gearing - Alexander N. Chukarin; Marina A. Gapova (Advanced Engineering Research)
The aim of this work is to find the methods of reducing noise and vibration in the belt drive of the electromechanical drive of the selected technological equipment. Thus, we are having more comfortable working conditions in the workplace in compliance with the sanitary standards of noise and vibration. The noise abatement techniques and the simulation of the vibration of the grinding woodworker flexible gearing are considered. Modeling was performed with the introduction of Euler variables. The simulated dependences allow by calculation determine noise levels and load characteristics of the selected equipment. The comparison between the expected noise levels and the sanitary standards allow determining the exceedance and the sources of its generation. All this is the basis for selecting the engineering solutions to observe the noise code.